Human Resource Competence as a Moderating Variable in the Relationship between Digital Marketing Strategy and Restaurant Business Performance in Ambon City - Pieter Novry Ruddy Rehatta; Jacsy Tubalawony; Hadinda Hadinda; Hulawa Theresia Weileruny (Westscience Press, 2026)
This study aims to analyze the effect of digital marketing strategy on business performance and to examine the moderating role of human resource competence in the relationship between digital marketing strategy and business performance in the culinary industry of Ambon City, Indonesia. The study employed a quantitative explanatory research design involving 150 respondents consisting of owners, managers, and employees of culinary businesses. Data were collected using structured questionnaires based on a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The findings reveal that digital marketing strategy has a positive and significant effect on business performance. In addition, digital marketing strategy significantly